Coping, mood and health-related quality of life: a cross-sectional study in Chinese patients with advanced lung cancer. Issue 5 (5th May 2019) - He, Yaping; Jian, Hong; Yan, Meiqiong; Zhu, Jingfen; Li, Guohong; Lou, Vivian W Q; Chen, Jieling
Abstract : Objectives: The ways patients cope with advanced cancer can influence their health-related quality of life (HRQoL). This study aims to examine the mediating role of positive and negative mood in the relationship between coping and HRQoL in patients with advanced lung cancer. Methods: A consecutive sample of 261 patients (mean age: 59.99±9.53) diagnosed with stage III or IV lung cancer was recruited from the inpatient unit in a hospital that specialises in chest-related disease in Shanghai, China. Participants completed measurements including Medical Coping Modes Questionnaire, Positive and Negative Affect Schedule, and 5-level EuroQol 5-dimension instrument. Results: Although the total effects of confrontation on HRQoL were not significant, competing indirect effects via mood were identified: (1) positive indirect effects through positive mood were found for confrontation on mobility, usual activities, pain/discomfort and overall utility index (indirect effect=0.01, 95% CI 0.003 to 0.03); (2) negative indirect effects through negative mood were found for confrontation on mobility, pain/discomfort, anxiety/depression and overall utility index (indirect effect=−0.01, 95% CI −0.03 to −0.001). Resigned acceptance was negatively associated with HRQoL, and indirect effects via mood were identified: (1) negative indirect effects through positive mood were found for resigned acceptance on mobility, self-care, usual activities, pain/discomfort and overall utility index (indirect effect=−0.01, 95% CI −0.03 to −0.003); (2) negative indirect effects through negative mood were found for resigned acceptance on domains of HRQoL and overall utility index (indirect effect=−0.04, 95% CI −0.06 to −0.02). Conclusions: Confronting advanced lung cancer can fuel ambivalent emotional experiences. Nevertheless, accepting the illness in a resigned way can be maladaptive for health outcomes. The findings suggest interventions that facilitate adaptive coping, reduce negative mood and enhance positive mood, as this could help to improve or maintain HRQoL in patients with advanced lung cancer.